Examining critical factors affecting graduate retention from an emergency medicine training program in Addis Ababa, Ethiopia: a qualitative study of stakeholder perspectives - Kuipers, Meredith Jane; Eapen, Amira; Lockwood, Joel; Berman, Sara; Vaillancourt, Samuel; Maskalyk, James; Azazh, Aklilu; Landes, Megan (Canadian Medical Education Journal, 2017)
Background: In Ethiopia, improvement and innovation of the emergency care system is hindered by lack of specialist doctors trained in emergency medicine, underdeveloped emergency care infrastructure, and consumable resource limitations. Our aim was to examine the critical factors affecting retention of graduates from the Addis Ababa University (AAU) post-graduate emergency medicine (EM) training program within the Ethiopian health care system. Methods: Qualitative interviews were conducted with current AAU EM residents and stakeholders in Ethiopian EM. Mixed-methods inductive thematic analysis was performed. Results: Resident and stakeholder participants identified critical factors in three domains: the individual condition, the occupational environment, and the national context. Within each domain, priority themes emerged from the responses, including the importance of career satisfaction over the career continuum (individual condition), the opportunity to be involved in the developing EM program and challenges associated with resource, economic, and employment constraints (occupational environment), and perceptions regarding the state of awareness of EM and the capacity for change at the societal level (national context). Conclusions: This work underscores the need to resolve multiple systemic and cultural issues within the Ethiopian health care landscape in order to address EM graduate retention. It also highlights the potential success of a retention strategy focused on the career ambitions of keen EM doctors.